La and Ca-Doped A-Site Deficient Strontium Titanates Anode for Electrolyte Supported Direct Methane Solid Oxide Fuel Cell. Issue 9 (3rd August 2017) - Tiwari, Pankaj Kr.; Yue, Xiangling; Irvine, John T. S.; Basu, Suddhasatwa
Abstract : Nickel-yttria stabilized zirconia (Ni-YSZ) cermet anodes for solid oxide fuel cells (SOFC) possesses excellent catalytic properties and stability for H2 oxidation but not for hydrocarbons as it results in fast carbon deposition in absence of excess steam. In the present work, A-site deficient porous LSCTA- (La0.2 Sr0.25 Ca0.45 TiO3 ) anode has been fabricated using the environment friendly, aqueous tape casting method followed by the same procedure for the dense YSZ electrolyte and YSZ porous scaffold as cathode matrix. The anode, electrolyte, and porous cathode matrix have been laminated together and sintered up to 1350°C. After sintering, nitrate precursors of La, Sr, Co and Fe are infiltrated inside the porous YSZ cathode matrix to form the perovskite phases of La0.8 Sr0.2 CoO3 (LSC) and La0.8 Sr0.2 FeO3 (LSF). The as fabricated electrolyte supported SOFCs have been tested in H2 and CH4 fuel at 800°C. The electrolyte supported cell 15%LSF-5% LSC-YSZ/YSZ/4%Ni-6%CeO2 -LSCTA- gives maximum power density of 328 mW cm −2 for 3 h in H2, but in CH4 the performance decreased to 165 mW cm −2 even though a sustained open circuit voltage of ∼1 V obtained during H2 and CH4 operation. The morphology of the anode before and after cell testing has been analyzed using scanning electron microscope followed by X-ray diffraction studies to understand phase changes during fabrication and testing.